Engineered bacteria combined with doxorubicin nanoparticles suppress angiogenesis and metastasis in murine melanoma models. (1st March 2023) - Yang, Meiyang; Conceição, Mariana; Chen, Weijun; Yang, Fuwei; Zhao, Bingke; Wood, Matthew J.A.; Qiu, Lipeng; Chen, Jinghua
Abstract: Methods capable of distributing antitumour therapeutics uniformly throughout an entire tumour and that can suppress metastasis at the same time, would be of great significance in improving cancer treatment. Bacteria-mediated synergistic therapies have been explored for better specificity, temporal and spatial controllability, as well for providing regulation of the immune microenvironment, in order to provide improved cancer treatment. To achieve this goal, here we developed an engineered bacteria delivery system (GDOX@HSEc) using synthetic biology and interfacial chemistry technologies. The engineered bacteria were concurrently modified to express heparin sulfatase 1 (HSulf-1) inside (HSEc), to attach doxorubicin-loaded glycogen nanoparticles (GDOX NPs) on their surface. Here we demonstrate that HSEc can actively target and colonise tumour sites resulting in HSulf-1 overexpression, thereby suppressing angiogenesis and metastasis. Simultaneously, the GDOX NPs were able to penetrate into tumour cells, leading to intracellular DNA damage. Our results confirmed that a combination of biotherapy and chemotherapy using GDOX@HSEc resulted in significant melanoma suppression in murine models, with reduced side effects. This study provides a powerful platform for the simultaneous delivery of biomacromolecules and chemotherapeutic drugs to tumours, representing an innovative strategy potentially more effective in treating solid tumours. Statement of significance: An original engineered bacteria-based system (GDOX@HSEc) was developed using synthetic biology and interfacial chemistry technologies to concurrently produce naturally occurring heparin sulfatase 1 (HSulf-1) inside and anchor doxorubicin-loaded glycogen nanoparticles on the surface. GDOX@HSEc allowed for combined local delivery of chemotherapeutic agents along with the enzymes and immunostimulatory bacterial adjuvants, which resulted in a synergistic action in the inhibition of tumour growth and metastasis. The study provides a potential therapeutic approach that allows therapeutic agents to be distributed in a spatiotemporally controllable manner in tumours for combinatorial enhanced therapy. Graphical abstract: Image, graphical abstract